O saneamento cooperativo como roteiro de organização e de julgamento do processo - Gomes, Gustavo Gonçalves (2016)
The reorganization measures of the process is the main theme of the thesis .In spite of a classic theme, there are several influences and reconfigurations that need to be re-adjusted over time, the main focus remains to achieve the restructuring of the civil procedure: a fast and efficient guarantee of legal assistance. The study was developed with the methodical orientation of the deductive approach and the technical of the literature search. This study aims, in a first moment, reinforce the need of reorganization measures of the process regarding the organization and preparation of the lawsuit to the fnal phase and setting up the necessary rules, so that the process can reach its highest and best efficiency. Secondly, realize a new meaning of this well-known subject, with the provocations brought up hereby, which can be very useful to modernize the Brazilian Civil Process System. For this purpose, and before getting in the current reality, which is the result of the effectiveness of of Civil Procedure Code of 2015, we need to draw some considerations about the foreign influences on the issue and prepare a brief summary of the development of the reorganization measures in Brazilian’s law. It’s important to demonstrate, as well, objectively, the deficiencies in the previous model - the Civil Procedure Code of 1973 - and the reasons of its failure. In a brief conclusion, we can say that the absolute lack of awareness of the parties and the judges in the use of the old technical proposed in the previous procedural law was a major cause of loss of efficiency in the reorganization measures phase, which was completed with the "reorganization measure instruction". The innovations introduced by the Civil Procedure Code of 2015 promote the existence of a civil process in cooperation with several legal possibilities for the realization of a democratic and effective restructuring process, for the benefit of all parties involved in the process. The reorganization measures phase of the process and its decision serves as a judgment guide of the lawsuit, whose the content should be worked by the judge and the parties. In a law democratic state, it is right and appropriate to guarantee the “full right of adversarial exercise”; in particular, the judge must necessarily provide the parties (jointly or separately) the grounds of his judgment, based on the fact and the law. The Reorganization, in the context of procedural motion, is the main phase and enables the State, represented by the judge,to exercise the judicial activity in a technical manner, appropriate, effective and equitable